Improving Students' Information Competence Based On The Educational Module Of A Programming Course - Niyazov Feruz Xushboqovich; Pardayeva Dilfuza Najmiddin Kizi (Genius Journals, 2025)
This article addresses the issue of enhancing students' information competence based on programming course modules. The significance of ongoing reforms in Uzbekistan's education system regarding the study of modern information technologies and programming is highlighted. Suggestions are provided for teaching students how to search, analyze, and utilize information innovatively through programming modules. The theoretical and practical results of the research are recommended for use in the development of programming education
Keywords: mobile; methodology; information